Borrowing Constraints and Progress Through School: Evidence from Peru - Jacoby, Hanan G. (The Review of Economics and Statistics, 1994)
This paper investigates the effect of borrowing constraints on the timing of human capital investment in a developing country by looking at how quickly children with different family backgrounds progress through the primary school system in Peru. The main findings are that children start withdrawing from school earlier, as indicated by repetition of grades, in households with lower income and durable good holdings and when children are more closely spaced. Behavior also differs as predicted between children from households that appear to be borrowing constrained and those that appear unconstrained. Copyright 1994 by MIT Press.